DEVELOPMENT OF GEOLOCATION-BASED MOBILE APPLICATION FOR OPTIMIZED FREELANCE MAID SERVICE RECOMMENDATION - Saidi, R. M.; Omar Bashah, N. S. S.; Mohd Ghazalli, H. I.; Abdul Jalil, U. M.; Sharip, A. A. (Journal of Engineering and Technology (JET), 2026)
The increasing demand for freelance maids highlights the need for a streamlined platform to connect them with customers. This study presents the development of a Freelance Maid Application that utilizes geolocation and a recommendation system to simplify the hiring process. The objective of this project is to develop Freelance Maid Application using geolocation and recommendations system. The methodology involved five key steps: data collection, service selection, maid recommendation, booking selection, and confirmation. The application allows users to choose services, view top-rated maids, and complete bookings efficiently. Geolocation aids maid navigation, while customer ratings ensure service quality. Results indicate that the application enhances accessibility and reliability for both users and freelance maids. Customers can find nearby maids easily, while maids receive structured job requests. Future enhancements include FPX payment integration, a service rate recommendation system, and live location tracking to improve user experience. These features will further optimize the platform for a more efficient and convenient hiring process.